Bamboo-like N-doped carbon nanotube–confined cobalt as an efficient and robust catalyst for activating monopersulfate to degrade bisphenol A. (September 2021) - Nguyen, Ha Trang; Lee, Jechan; Kwon, Eilhann; Lisak, Grzegorz; Thanh, Bui Xuan; Ghanbari, Farshid; Lin, Kun-Yi Andrew
Abstract: As bisphenol A (BPA) is an extensively used chemical for manufacturing plastic products, discharge of BPA into the environment has caused serious threats to ecology. Therefore, -based chemical oxidation methods have been employed for eliminating BPA. Because monopersulfate (MNP) has become a popular reagent for obtaining, and Co is the most efficient metal for activating MNP, it is critical to develop heterogeneous Co catalysts for easier implementation and recovery. Herein, a unique Co-based catalyst is proposed by utilizing tubular-structured N-doped carbon substrates, derived dicyandiamide (DCDA), to confine Co nanoparticles (NPs). Through simple pyrolysis of a mixture of Co/DCDA, DCDA would be transformed into N-doped carbon nanotubes (CNT) to wrap the resultant Co NP, and, interestingly, this N-doped CNT would exhibit a special bamboo-like morphology. More importantly, as Co NPs are mono-dispersed and singly-confined in N-doped CNTs, forming CoCNT, CoCNT exhibits significantly higher catalytic activities than Co3 O4, for activating MNP to degrade BPA. The enhancement of catalytic activities in CoCNT would be possibly ascribed to the synergistic effects between Co NP and the N-doped CNT which not only acts as the support/protection but also provides active sites. Therefore, CoCNT + MNP could lead to a much lower E a ( i.e., 13.8 kJ/mol) of BPA degradation than the reported E a values. Besides, CoCNT is still effective for eliminating BPA even in the presence of high-concentration NaCl and surfactants. CoCNT is also reusable over many cycles and retains its catalytic activity with 100% BPA removal, demonstrating that CoCNT is an advantageous and robust catalyst for MNP activation. Graphical abstract: Image 1 Highlights: Co/DCDA is converted to Co-confined in N-doped carbon nanotube (CoCNT). CoCNT exhibits a higher catalytic activity than pristine Co3 O4 NPs for activating MNP. CoCNT + MNP also achieves a significantly lower E a value of BSP degradation. CoCNT is effective for elimination of BSP in the presence of NaCl/surfactants. CoCNT is also reusable over many cycles and remains highly catalytically active.